2021
DOI: 10.3389/fphar.2020.518225
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a Vital Therapy Target for Renal Cell Carcinoma

Abstract: Autophagy is a process that degrades and recycles superfluous organelles or damaged cellular contents. It has been found to have dual functions in renal cell carcinoma (RCC). Many autophagy-related proteins are regarded as prognostic markers of RCC. Researchers have attempted to explore synthetic and phytochemical drugs for RCC therapy that target autophagy. In this review, we highlight the importance of autophagy in RCC and potential treatments related to autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Autophagy is an essential procedure in the biological function accomplishment of ccRCC [ 24 ]. The autophagy-related genes, signaling pathways, and markers are associated with ccRCC, and to further analyze the inner link between autophagy molecules to clarify conversion between autophagy and apoptosis, they can provide new ways for an early diagnosis on ccRCC and provide novel strategy to clinical treatment [ 10 , 24 , 25 ]. In this study, large-scale gene expression profile was paged for the investigation on the association within autophagy-related genes and clinicopathological characteristics, as well as OS in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an essential procedure in the biological function accomplishment of ccRCC [ 24 ]. The autophagy-related genes, signaling pathways, and markers are associated with ccRCC, and to further analyze the inner link between autophagy molecules to clarify conversion between autophagy and apoptosis, they can provide new ways for an early diagnosis on ccRCC and provide novel strategy to clinical treatment [ 10 , 24 , 25 ]. In this study, large-scale gene expression profile was paged for the investigation on the association within autophagy-related genes and clinicopathological characteristics, as well as OS in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been reported to be either inhibiting or promoting tumor progression by changing the malignant behavior of tumor cells, implying it is a very important mechanism for cell invasion and metastasis, angiogenesis, or tumorigenesis. In other words, it is suggested that lack of autophagy in tumor cells causes tumor suppression or tumorigenesis through different mechanisms [ 11 , 33 , 34 ]. Interferons (IFNs) induce the expression of interferon-stimulated genes (ISGs) and play a critical role in innate immune response against numerous viral infections by inhibiting autophagy [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in renal cancer is not yet fully explained. While some in vivo studies demonstrated that the induction of autophagy is capable of activating apoptosis in precancerous cells, other authors argue that the intensification of autophagy during chemotherapy may facilitate tumor survival and hence accelerate tumor progression [ 67 , 68 , 69 , 70 ]. Despite its dual role in carcinogenesis, autophagy has been recently suggested as a therapeutic target for renal cancer [ 4 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some in vivo studies demonstrated that the induction of autophagy is capable of activating apoptosis in precancerous cells, other authors argue that the intensification of autophagy during chemotherapy may facilitate tumor survival and hence accelerate tumor progression [ 67 , 68 , 69 , 70 ]. Despite its dual role in carcinogenesis, autophagy has been recently suggested as a therapeutic target for renal cancer [ 4 , 69 ]. The rationale is based on the fact that RCC cells exhibit an elevated basal level of autophagy, can alleviate periods of therapy-induced stress, and promote drug and radiation resistance [ 66 , 71 ] ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%